2013
DOI: 10.3389/fncel.2013.00207
|View full text |Cite
|
Sign up to set email alerts
|

Impaired rRNA synthesis triggers homeostatic responses in hippocampal neurons

Abstract: Decreased rRNA synthesis and nucleolar disruption, known as nucleolar stress, are primary signs of cellular stress associated with aging and neurodegenerative disorders. Silencing of rDNA occurs during early stages of Alzheimer's disease (AD) and may play a role in dementia. Moreover, aberrant regulation of the protein synthesis machinery is present in the brain of suicide victims and implicates the epigenetic modulation of rRNA. Recently, we developed unique mouse models characterized by nucleolar stress in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…UBF encoded by UBTF (upstream binding transcription factor, RNA polymerase I gene) is associated with NOR and is required for rDNA transcription by RNA polymerase 1 (83). It is known that altered expression of nucleolar chaperones and factors involved in rRNA synthesis results in nucleolar stress which in turn leads to impaired ribosomal biogenesis (4,58,69,79). The present observations show nucleolar stress in the hippocampus, mainly in CA1 but also in DG, in AD.…”
Section: Nucleolar Alterationsmentioning
confidence: 44%
“…UBF encoded by UBTF (upstream binding transcription factor, RNA polymerase I gene) is associated with NOR and is required for rDNA transcription by RNA polymerase 1 (83). It is known that altered expression of nucleolar chaperones and factors involved in rRNA synthesis results in nucleolar stress which in turn leads to impaired ribosomal biogenesis (4,58,69,79). The present observations show nucleolar stress in the hippocampus, mainly in CA1 but also in DG, in AD.…”
Section: Nucleolar Alterationsmentioning
confidence: 44%
“…In addition, it promotes p53-mediated apoptosis [74]. The depletion of TIF-IA in adult hippocampal neurons, however, has no impact on the survival of neural cells [75]. Hence, apoptosis induced by TIF-IA depletion is cell-type dependent.…”
Section: The Effects Of Tif-ia Deletionmentioning
confidence: 99%
“…28 Targeted deletion of TIF-IA in adult mouse hippocampus neurons induces a protracted neuronal degeneration, whereas in embryonic neural progenitors, it triggers a rapid apoptosis. 29,30 These observations suggested that the conditional ablation of TIF-IA could be used as a genetic tool to induce a protracted suicide response in slowly dividing or post-mitotic cells. Here, we report the development of a novel inducible b-cell loss model, based on the conditional ablation of TIF-IA, in which b-cell death occurs gradually and over a longer period of time compared to previously used animal models.…”
Section: Introductionmentioning
confidence: 99%